Família-escola : um olhar sobre a participação da família no contexto da EMEF Waldir Ribeiro de Almeida em Novo Repartimento Pa - SANTANA, Jurdilene da Luz (2019)
This present work carried out a field study of education, a Municipal School of Waldir Ribeiro de Almeida, in the municipality of Novo Repartimento (PA). The purpose of this study was to analyze the importance of family participation without school context. For an evaluation of this work, a field observation and data collection were conducted in the form of interviews, where parents and teachers could express their opinions about the participation of the family in the school. A school survey of pupils' school attendance, participation in school, a family relationship with a school, a family form, participates in their children's school education, as well as country views on the importance. of the family. The results show that parents and teachers share the same interest in achieving a greater exchange between family and school, in the end stores most of the parts for which they are a portion.